Investigation of Hospital Waiting Areas for Children’s Wellbeing Through Components of Interior Design in Northern Cyprus and Kuwait - Baouassi, Christine (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
This study aims to investigate the impact of interior design components such as colour, material, light, and furniture on the well-being of children in hospital waiting areas. The research focuses on children’s perception of space and their sense of belonging and safety within these spaces. The study also explores how different components of interior space, including colour, artificial lighting, materials, textures, furniture and fixtures options, can influence a child’s well-being in these settings. This study will conduct case studies in selected children’s hospitals in Northern Cyprus and Kuwait. The case studies in these two distinct regions were chosen to understand the influence of cultural and regional differences on the effectiveness of interior design components. Northern Cyprus faces challenges in providing quality healthcare, especially for children, while Kuwait’s healthcare sector has seen significant growth. The study will compare the psychological effects and spatial findings in paediatric hospitals in these two countries. The research is limited to five hospitals in each country for diverse and comparative research. The recommendations provided in this study are based on general developmental theories and may not necessarily apply to all children. Every child is unique and may have their individual preferences and needs that may not be fully addressed by the design recommendations provided in this study. Therefore, it is important to consider the specific needs of each child and their family when designing waiting room sections. The findings of this research are intended to guide designers in creating more child-friendly hospital spaces, thereby enhancing the well-being of children during their hospital visits.

ÖZ: Bu çalışma, hastane bekleme alanlarındaki renk, malzeme, ışık ve mobilya gibi iç tasarım bileşenlerinin çocukların refahı üzerindeki etkisini araştırmayı amaçlamaktadır. Araştırma, çocukların mekân algısına, bu mekânlara ait olma ve güvenlik duygularına odaklanıyor. Çalışma aynı zamanda renk, yapay aydınlatma, malzeme, doku, mobilya ve demirbaş seçenekleri de dahil olmak üzere iç mekanın farklı bileşenlerinin bu ortamlarda çocuğun refahını nasıl etkileyebileceğini araştırıyor. Bu çalışma, aşağıdaki gibi iç tasarım bileşenlerinin etkisini araştırmayı amaçlamaktadır: hastane bekleme alanlarındaki çocukların refahı üzerinde renk, malzeme, ışık ve mobilya. Araştırma, çocukların mekân algısına, bu mekânlara ait olma ve güvenlik duygularına odaklanıyor. Çalışma aynı zamanda renk, yapay aydınlatma, malzemeler, dokular, mobilya ve demirbaş seçenekleri dahil olmak üzere iç mekanın farklı bileşenlerinin bu ortamlarda çocuğun refahını nasıl etkileyebileceğini de araştırıyor. Bu çalışmada Kuzey Kıbrıs ve Kuveyt'teki seçilmiş çocuk hastanelerinde vaka çalışmaları yapılacaktır. Bu iki farklı bölgedeki örnek olay çalışmaları, kültürel ve bölgesel farklılıkların iç tasarım bileşenlerinin etkinliği üzerindeki etkisini anlamak için seçilmiştir. Kuzey Kıbrıs, özellikle çocuklara kaliteli sağlık hizmeti sağlama konusunda zorluklarla karşı karşıyayken, Kuveyt'in sağlık sektörü önemli bir büyüme kaydetti. Çalışmada bu iki ülkedeki çocuk hastanelerindeki psikolojik etkiler ve mekânsal bulgular karşılaştırılacaktır. Araştırma, çeşitli ve karşılaştırmalı araştırmalar için her ülkedeki beş hastane ile sınırlıdır.Bu çalışmada sunulan öneriler genel gelişim teorilerine dayanmaktadır ve tüm çocuklar için geçerli olmayabilir. Her çocuk benzersizdir ve bu çalışmada sunulan tasarım önerilerinin tam olarak karşılayamadığı bireysel tercihleri ve ihtiyaçları olabilir. Bu nedenle bekleme odası bölümleri tasarlanırken her çocuğun ve ailesinin özel ihtiyaçlarının dikkate alınması önemlidir. Bu araştırmanın bulgularının, tasarımcılara daha çocuk dostu hastane alanları yaratma konusunda rehberlik etmesi ve böylece çocukların hastane ziyaretleri sırasında refahını artırması amaçlanıyor.
Master of Science in Interior Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2024. Supervisor: Asst. Prof. Dr. Ahenk Yılgın Damgacı
Keywords: Interior Architecture Department; Hospitals--Architecture and Design--Interior Decoration; Health facilities--Decoration; Interior Design--Hospitals--Health Centers--Children--Kuwait--Cyprus (Turkish Republic of Northern Cyprus, 1983-); hospital interior space, waiting area, well-being, interior design components, sense of belonging